2019
DOI: 10.1080/14756366.2019.1664499
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro and in vivo anti-inflammatory activity of novel 4-ferrocenylchroman-2-one derivatives

Abstract: A series of novel 4-ferrocenylchroman-2-one derivatives were designed and synthesised to discover potent anti-inflammatory agents for treatment of arthritis. All the target compounds had been screened for their anti-inflammatory activity by evaluating the inhibition effect of LPS-induced NO production in RAW 264.7 macrophages. Among them, 4-ferrocenyl-3,4-dihydro-2H-benzo[g]chromen-2-one (3h) was found to be the most potent compound in inhibiting the productions of NO with low toxicity. This compound also exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To establish an arthritis model, we used Freund’s complete adjuvant to induce arthritis in rats via injection of CFA into the left hind paw of rats 53 , 54 . After injection of CFA into SD rats, the results showed that 80–90% of the rats showed paw swelling within 14–28 days ( Figure 6 , model group).…”
Section: Resultsmentioning
confidence: 99%
“…To establish an arthritis model, we used Freund’s complete adjuvant to induce arthritis in rats via injection of CFA into the left hind paw of rats 53 , 54 . After injection of CFA into SD rats, the results showed that 80–90% of the rats showed paw swelling within 14–28 days ( Figure 6 , model group).…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of the proinflammatory mediator, NO participates in many kinds of inflammatory reactions . Therefore, it has been established that the ability of compounds to inhibit NO overproduction could be used to assess anti-inflammatory effects. As shown in Figure d, the production of NO of LPS-treated RAW264.7 cells remarkably increased six times compared with that of control cells. In the absence of LPS stimulation, the Rhein solution group showed no effect on NO secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The design and synthesis of some novel anti‐inflammatory 4‐ferrocenylchroman‐2‐one derivatives (Scheme 19) for the treatment of arthritis was reported by Guo et al [ 59 ] The screening of the compounds was performed to determine the anti‐inflammatory effect by inhibition of LPS induced NO production in RAW 264.7 macrophages. The SAR was also developed and it was found that NO inhibitory activity increases on introducing coplanar groups like naphthalenyl ( 24 ) (Figure 15) and benzodioxol bridging to the dihydrocoumarin ring.…”
Section: Development Of Antiarthritic Agents So Farmentioning
confidence: 99%